2001
DOI: 10.1074/jbc.m011068200
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Molecular Model for Modulation of Mammalian Translation by the eIF4E-binding Protein 1

Abstract: Translation initiation is a key point of regulation in eukaryotic gene expression. 4E-binding proteins (4E-BPs) inhibit initiation by blocking the association of eIF4E with eIF4G, two integral components of the mRNA cap-binding complex. Phosphorylation of 4E-BP1 reduces its ability to bind to eIF4E and thereby to compete with eIF4G. A novel combination of biophysical and biochemical tools was used to measure the impact of phosphorylation and acidic side chain substitution at each potentially modulatory site in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 48 publications
8
71
1
Order By: Relevance
“…Recently, several reports have shown that p53 is able to induce or activate novel protein phosphatases (Li et al, 2003;Ueda et al, 2003;Yin et al, 2003) but whether any of these act on 4E-BP1 remains to be established. It may be significant that the greatest p53-induced loss of phosphate from 4E-BP1 in vivo appears to involve Ser 64 , since this site can have a large influence on the binding of the protein to eIF4E (Mothe-Satney et al, 2000b;Karim et al, 2001) (although this conclusion has been challenged; Ferguson et al, 2003). 4E-BP1 is phosphorylated in a hierarchical fashion, with Ser 64 being the last site to be modified when cells are stimulated by serum (Gingras et al, 1999a(Gingras et al, , 2001a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several reports have shown that p53 is able to induce or activate novel protein phosphatases (Li et al, 2003;Ueda et al, 2003;Yin et al, 2003) but whether any of these act on 4E-BP1 remains to be established. It may be significant that the greatest p53-induced loss of phosphate from 4E-BP1 in vivo appears to involve Ser 64 , since this site can have a large influence on the binding of the protein to eIF4E (Mothe-Satney et al, 2000b;Karim et al, 2001) (although this conclusion has been challenged; Ferguson et al, 2003). 4E-BP1 is phosphorylated in a hierarchical fashion, with Ser 64 being the last site to be modified when cells are stimulated by serum (Gingras et al, 1999a(Gingras et al, , 2001a.…”
Section: Discussionmentioning
confidence: 99%
“…Hypophosphorylated 4E-BP1 binds to eIF4E in competition with eIF4GI or II, thus decreasing the availability of the eIF4F complex for initiation of translation (Marcotrigiano et al, 1999;Karim et al, 2001). We have reported previously that when cells expressing the Val 135 mutant form of p53 are incubated at 321C to activate the tumour suppressor, extensive 4E-BP1 dephosphorylation occurs.…”
Section: Dephosphorylation and Modification Of 4e-bp1 Following P53 Amentioning
confidence: 99%
See 1 more Smart Citation
“…Although both phosphorylated and nonphosphorylated eIF-4E bind to the mRNA cap structure, phosphorylation of eIF-4E enhances the affinity of the factor for the m 7 GTP cap by severalfold (39). Furthermore, in vitro studies have demonstrated that increases in eIF-4E phosphorylation are proportional to increases in the rate of translation (23). Conversely, a decrease in eIF-4E phosphorylation has been correlated with a reduction in protein synthesis after viral infection (13).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of 4E-BP1 greatly decreases the affinity of 4E-BP1 for eIF-4E and leads to dissociation of the 4E-BP1 ⅐ eIF-4E complex (23). This permits the formation of a competent eIF-4F complex and the stimulation of initiation.…”
Section: Discussionmentioning
confidence: 99%